2020
DOI: 10.1093/jxb/eraa539
|View full text |Cite
|
Sign up to set email alerts
|

The role of CLAVATA signalling in the negative regulation of mycorrhizal colonization and nitrogen response of tomato

Abstract: Plants form mutualistic nutrient acquiring symbioses with microbes, including arbuscular mycorrhizal fungi. The formation of these symbioses is costly and plants employ a negative feedback loop termed autoregulation of mycorrhizae (AOM) to limit arbuscular mycorrhizae (AM) formation. We provide evidence for the role of one leucine-rich-repeat receptor like kinase (FAB), a hydroxyproline O-arabinosyltransferase enzyme (FIN) and additional evidence for one receptor like protein (SlCLV2) in the negative regulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 89 publications
(92 reference statements)
5
34
0
Order By: Relevance
“…In tomato, clv2 mutants exhibit increased mycorrhizal colonization rates (Wang et al, 2018). Moreover, grafting experiments using tomato clv2 demonstrated that CLV2 might act in both the shoot and roots to regulate AMF colonization (Wang et al, 2021). Since CLV2 physically interacts with shoot-acting LRR-RLK of legumes such as SUNN via CORYNE in M. truncatula (Crook et al, 2016), further investigation of the relationship between CLV2 and AM symbiosis in non-legumes is required.…”
Section: Future Perspectivementioning
confidence: 99%
“…In tomato, clv2 mutants exhibit increased mycorrhizal colonization rates (Wang et al, 2018). Moreover, grafting experiments using tomato clv2 demonstrated that CLV2 might act in both the shoot and roots to regulate AMF colonization (Wang et al, 2021). Since CLV2 physically interacts with shoot-acting LRR-RLK of legumes such as SUNN via CORYNE in M. truncatula (Crook et al, 2016), further investigation of the relationship between CLV2 and AM symbiosis in non-legumes is required.…”
Section: Future Perspectivementioning
confidence: 99%
“…By contrast, CLE peptides have been established as negative regulators of RN and AM symbiosis. Several genes encoding CLE peptides were found to be induced in roots in response to plant interactions with both AM fungi and rhizobia, as well as with macronutrients, such as N and P [9,10,[20][21][22][23][24]. Fully processed CLE peptides are 12-13-amino acids long and often posttranslationally modified by proline hydroxylation and arabinosylation [25].…”
Section: Trends Trends In In Plant Plant Science Sciencementioning
confidence: 99%
“…These LRR-RLKs act as negative regulators of RN and AM symbiosis [29, [46][47][48][49][50][51][52]. Interestingly, this phenomenon does not appear to be only specific to legumes, because CLV1 orthologs in the non-legumes Brachypodium distachyon and tomato were recently reported to act as negative regulators of AM [9,23]. Although no functional connection to AM-induced CLE signaling was demonstrated in these species, these findings suggest that autoregulation of symbiosis is conserved across plant clades.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations